Evaluasi Sistem Proporsional Terbuka Pemilu Legislatif Berdasarkan Teori Struktural Hukum Pemilu Issacharoff - Rahim, Erman I.; Imran, Hendrik; Abdussamad, Zamroni; Piyo, Sofyan (Universitas Islam Indonesia, 2025)
The open proportional system implemented in Indonesia since the 2009 elections was designed to enhance democratic participation and strengthen legislative accountability. Nevertheless, in practice, this electoral model has produced structural problems that have significantly undermined the quality of representative democracy. This study seeks to address a critical question: to what extent does the open proportional system generate structural imbalances in the distribution of political power within Indonesia’s democratic framework? A normative legal method is employed, utilizing the Structural Approach to Election Law developed by Samuel Issacharoff and refined by Nicholas Stephanopoulos and Yasmin Dawood. The research is based on doctrinal analysis of election laws, Constitutional Court decisions, relevant legal literature, and democratic theory. The findings indicate that the system reinforces the dominance of wealthy candidates, erodes the ideological foundations of political parties, and perpetuates structural exclusion of marginalized social groups. Furthermore, it demonstrates that election law, as an institutional structure, is not ideologically neutral and may be exploited to preserve unequal power relations. The study concludes that electoral reform is necessary to achieve structural justice, particularly through the reconstruction of electoral districts, revision of the parliamentary threshold, implementation of transparent campaign finance regulations, and revitalization of political parties as ideological entities. The structural approach offers a critical and holistic analytical framework for building a more just, inclusive, and substantively democratic electoral system in Indonesia.